2020
DOI: 10.3389/fphys.2020.00473
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Inflammatory Hyperalgesia Depends on P2X7 Receptors in Satellite Glial Cells

Abstract: Peripheral inflammatory hyperalgesia depends on the sensitization of primary nociceptive neurons. Inflammation drives molecular alterations not only locally but also in the dorsal root ganglion (DRG) where interleukin-1 beta (IL-1β) and purinoceptors are upregulated. Activation of the P2X7 purinoceptors by ATP is essential for IL-1β maturation and release. At the DRG, P2X7R are expressed by satellite glial cells (SGCs) surrounding sensory neurons soma. Although SGCs have no projections outside the sensory gang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 94 publications
2
18
0
7
Order By: Relevance
“…A large number of studies have suggested that the up-regulation of P2 × 7R is involved in the cancer and neuropathic pain [25,[84][85][86][87][88]. Here, we reported increase in the expression of microglial P2 × 7R in the TNC area and con rmed the relationship between P2 × 7R and CM.…”
Section: Discussionsupporting
confidence: 80%
“…A large number of studies have suggested that the up-regulation of P2 × 7R is involved in the cancer and neuropathic pain [25,[84][85][86][87][88]. Here, we reported increase in the expression of microglial P2 × 7R in the TNC area and con rmed the relationship between P2 × 7R and CM.…”
Section: Discussionsupporting
confidence: 80%
“…Inhibition of NETosis by YW3-56 can reduce the expression of MST1, YAP and the release of IL-1β by microglia, indicating that NETs contribute to the activation of microglia and IL-1β secretion in the PVN. A previous study also found that activation of the P2 × 7 purinoceptors in the glial cell is essential for IL-1β release ( Neves et al, 2020 ). Besides, Zhao et al (2016) found that the Hippo/MSTI signaling pathway can regulate microglial activation.…”
Section: Discussionmentioning
confidence: 86%
“…They also showed that exercise reversed nerve injury-induced BDNF upregulation and glial hyperactivity on dorsal root ganglion (DRG), which can also be used as background to explain the mechanism of the exercise-induced analgesia showed in the present study. In this context, it is important to mention that DRG glial activation is required for the PGE 2 -induced hyperalgesia [ 43 , 44 ], which suggest that the analgesia induced by exercise observed in the present study could be mediated by a DRG glial mechanism.…”
Section: Discussionmentioning
confidence: 89%